Red sky mourning : a thriller [large type] - Carr, Jack (Joint pseudonym) (Carr, Jack (Joint pseudonym). Terminal list (Series), 2024)
"A storm is on the horizon. America's days are numbered. A Chinese submarine has gone rogue and is navigating towards the continental United States, putting its nuclear missiles within striking distance of the West Coast. A rising Silicon Valley tech mogul with unknown allegiances is at the forefront of a revolution in quantum computing and Artificial Intelligence. A politician controlled by a foreign power is a breath away from the Oval Office. Three seemingly disconnected events are on a collision course to ignite a power grab unlike anything the world has ever seen. The country's only hope is a quantum computer that has gone dark, retreating to the deepest levels of the internet, learning at a rate inconceivable at her inception. But during her time in hiding, she has done more than learn. She has become a weapon. She is now positioned to act as either the country's greatest savior or its worst enemy. She is known as Alice and her only connection to the outside world is to a former Navy SEAL sniper named James Reece, who has left the violence of his past life behind. Will there be blood? Count on it!"--